EDUKASI MENINGKATKAN PEMAHAMAN ANAK TENTANG PERAN PEMERINTAH SEBAGAI BENTUK TANGGUNG JAWAB WARGA NEGARA - Rahmadani, Rahmadani; Zulyan, Zulyan (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This activity aims to increase elementary school children's awareness of the role of government as a form of citizen responsibility through outreach activities. The methods used include interactive approaches such as lectures, group discussions, educational games, and role simulations. The results of this activity show that this interactive method is effective in increasing students' understanding of the important role of government in society. Children become more aware of their responsibilities as citizens, understanding the government's duties in providing public services, maintaining order, and organizing various aspects of life for the common good